Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods

Structural evolutions of hydrothermally prepared mesostructured MCM-48 silica using differently manufactured amorphous silica powders - Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N. (Journal of Non-Crystalline Solids, 2007)
The hydrothermal synthesis of Si-MCM-48 mesoporous molecular sieves was carried out using a ternary SiO2:CTAOH:H2O System wherein differently manufactured amorphous silica powders such as fumed silica (FMDS), spray dried precipitated silica (SDPS) and flash dried precipitated silica (FDPS) were used as silica source materials. The changes in structural/textural properties were evaluated using powder XRD, N-2 adsorption-desorption and scanning electron microscopy techniques. Studies on the progressive development of MCM-48 mesophases revealed that, the reactivity of the silica source follow the trend: FMDS > SDPS > FDPS. MCM-48 synthesized using low cost FDPS has exhibited thicker pore walls but poorer orderness, while MCM-48 prepared from relatively expensive FMDS has thinner pore walls and more ordered structure. Moreover, the extent of contraction caused by calcinations, agglomerate size and structural stability were found to depend on the reactivity of the silica source used. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: long-range order; micelles; scanning electron microscopy; silica; silicates; sol-gels (xerogels); X-ray diffraction